2019
DOI: 10.1186/s13046-019-1126-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeting late-stage non-small cell lung cancer with a combination of DNT cellular therapy and PD-1 checkpoint blockade

Abstract: BackgroundThough immune checkpoint blockade (ICB) against PD-1 has shown success in the treatment of lung cancer, not all patients respond. We have previously shown that adoptive transfer of double negative T (DNT) cells expanded from healthy donors can target leukemia but their role in treating established lung cancer is not clear. Here we explore the role of human DNT cells in targeting late-stage established lung cancer either alone or in combination with Nivolumab (anti-PD-1 antibody) and describe underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 49 publications
1
53
0
1
Order By: Relevance
“…48 DNTs have been previously reported to contribute to antimelanoma immunity. 49 In addition, this immunomodulatory effect is congruent with the reduced frequency of CD4 + T cell subpopulation as DNTs have been shown to suppress metabolic activation of CD4 + T cells (53) and could account for the CD4 + T cell reduction in this study. Nevertheless, the contribution of DNTs to antitumor immunity has only begun to be considered.…”
Section: Discussionsupporting
confidence: 70%
“…48 DNTs have been previously reported to contribute to antimelanoma immunity. 49 In addition, this immunomodulatory effect is congruent with the reduced frequency of CD4 + T cell subpopulation as DNTs have been shown to suppress metabolic activation of CD4 + T cells (53) and could account for the CD4 + T cell reduction in this study. Nevertheless, the contribution of DNTs to antitumor immunity has only begun to be considered.…”
Section: Discussionsupporting
confidence: 70%
“…Yao J et al [68] recently reported that IL-15 enhanced the killing effect of DNTs. Fang et al [69] showed that DNT tumor infiltration increased when combined with anti-PD-1 treatment, which enhanced DNT cell-mediated antitumor effects. Andrea Ponzetta et al [70] studied the role of DNTs in the tumor microenvironment and found that neutrophils can regulate the function of αβ+DNTs and that αβ+DNTs may have an essential role in antitumor immunity.…”
Section: Recent Progress In Dnt-based Immunotherapymentioning
confidence: 99%
“…DNTs combined with PD-1 inhibitor therapy achieve better efficacy. Fang et al [69] found that allogeneic DNTs from healthy donors killed lung cancer cells, and the combination of a PD-1 inhibitor increased the proportion of DNT infiltration in lung cancer tissues, thus inhibiting the growth of transplanted tumors in mice. These results show that adoptive infusion of DNTs may be a promising option for chemotherapy-resistant cancer, and the combination of DNTs with PD-1 inhibitor therapy may achieve better efficacy than either treatment alone.…”
Section: Applications Of Dntsmentioning
confidence: 99%
See 1 more Smart Citation
“…To complement the general role of control and surveillance of malignant cells that the immune system play, the development of adoptive cellular therapy and checkpoint blockade has brought about a revolution in the landscape of cancer therapy and promises the potential in which oncologists can utilize a patient’s immune system to treat cancer. 185 , 261 263 Purinergic signaling axis has gained prominence as one of the mechanisms of tumor-mediated immunosuppressions, in which the purine nucleoside adenosine produced in the TME has the ability of potently suppressing NK cell function. 264 – 266 During this event, the production of extracellular adenosine is triggered by the mediation of the cell surface ectoenzymes CD38, CD39, and CD73, 267 269 and the development of therapeutic agents has focused on targeting these enzymes as responses.…”
Section: Study and Progress Of Adenosine In The Nk Cell Cancer Immunomentioning
confidence: 99%